Le continent noir du désir masculin : Colet et Flaubert, encore - Barbara Vinken (Flaubert: Revue Critique et Génétique)
Few correspondences are as distressingly surprising to the reader as the letters between Louise Colet and Gustave Flaubert. The hope entertained by every reader of a happy love story has rarely been so disappointed. The studies on sexuality by Freud, one of the greatest skeptics on the subject of love, shed light on the vicissitudes of masculine desire. Flaubert’s letters to Colet are the dramatization of a desire conforming to kinks of a fetishist scenario. The fetish is the slippers in which Colet’s bloodstained handkerchief is thrust and then used by Flaubert to masturbate. The investing of this fetish object is only the more evident, you might even say clinical, symptom of this fetishist disposition. According to these letters masturbation, linked to foot and shoe fetishism, was Flaubert’s most satisfying sexual practice. The tragedy of castration is embodied in the slippers, a childish way of interpreting sexual difference. On the one hand the slippers are what the child sees before becoming aware of the absence of the maternal penis. The slippers, a most classic fetish, by a metonymic displacement take the place of the maternal phallus, whose absence is discovered with horror. This lack makes the boy realize the possibility of castration. The fetish object is both memory of and triumph over castration. Flaubert’s fetish bears the mark of castration: the blood stains. They both witness and screen the wound. Nothing excites Flaubert as much as these slippers, which together deny (Verleugnung) and acknowledge castration. As Freud writes, the fetishist does not only adore the fetish. Often castration is inscribed in the object. Flaubert expresses his inability to love on the one hand by his extreme male chauvinistic and hygienic practice of “baisade” or “foutrerie”, and on the other, in a ascetic, even monastic, discourse of “life for Art”, or, even better, of an Art that demands dying to life. Such words are only a screen to hide an agonizing drama which he never wants to experience again. For it would mean being torn once more between castration and loss of the love object. This is a conflict which he believes he resolved once and for all in what has traditionally been called his crisis. Flaubert is already castrated and dead. In Art he can gamble and lose what he could preserve in life only at the cost of love: his virility. Flaubert displaces onto writing the castration of love. He produces a work, a phallic corpus, from which everything feminine – limp, flabby, dripping – must be scrupulously removed. But this corpus, shaped in his stylistic work by the physiological model of the masculine sex, reveals a desperate identification with men and women mortally wounded by love. This love wound often carries religious connotations. Thus, contrary to what has often been claimed, the Flaubertian text is not a assertion of his virility. Rather, it would be both a performance of and a triumph over the castration drama.